Gender and Couple Relationships - McHale, Susan M.; King, Valarie; Van Hook, Jennifer; Booth, Alan (National Symposium on Family Issues, 2016)
This provocative volume is comprised of psychological, socioeconomic, and cultural perspectives on couple dynamics, particularly gender dynamics, and the future of marriage. Featuring data on married, cohabitating, male/female, and same-sex couples, the authors of the book's chapters analyze the changing impacts of work, parenting, and the health benefits of marriage for men and women. Trajectories in the evolution toward gender equality provide the backdrop for discussions of women and men as partners, parents, and workers in contemporary society. Contributors also keep a sharp focus on the complexities of gender issues as they intersect with crucial contexts of cohort, class, race/ethnicity, and sexual orientation.   Among the topics covered:   Gender equality and economic inequality: impacts on marriage. Expansionist theory expanded: integrating sociological and psychological perspectives on gender, work, and family change. Gender, work, and family: action in the interactions. Changes in U.S. mothers' and fathers' time use: causes and consequences. A case for gay fathers. Gender, marriage, and health for same-sex and different-sex couples   Gender and Couple Relationships documents social roles and social change with fascinating insight to advance research in fields of psychology, sociology, demography and economics and to the benefit of work organizations, policy makers, family and couple therapists and other mental health professionals.